Prognóza úrovně perinatální péče v České republice do nejbližší budoucnosti. I., Z pohledu vývoje ukazatelů v ČR - Štembera, Zdeněk; Velebil, Petr (Česká gynekologie, 2011)
Prognosis of the development of perinatal care in the Czech Republic in near future. STUDY DESIGN: Nation-wide perinatal epidemiological study. SETTING: Institute for the Care of Mother and Child, Prague-Podoli. METHODS: Four basic conditions for prognosis: previous prognosis, current status (previous and actual nationwide perinatal data), current environment, and international data for comparison. RESULTS: Prognosis of the Czechoslovak Academy of Science from the beginning of eighties to lower perinatal mortality from 15/1000 to 10/1000 until the year 2000 was accomplished already in 1989. Prognosis of Scientific Board of the Czech Ministry of Health from 2004 analyzed in the first part the causes of improvement of perinatal mortality before and after 1990 and the reasons for increase of newborns under 2000 grams and cesarean sections in 90s. The second part of this prognosis predicted stagnation of perinatal mortality around 4/1000 until the year 2000 and postulated two alternatives for low birth-weight rate from 5.9% to a) 6.9% and b) 8.0% and cesarean section rates increase from 13.5% to a) 17% and b) 22%. This projection was based on previous two prognoses, on the data from the year 2000, and on the analysis of demographic and economic circumstances, and on the comparison of international perinatal data. According to the prognosis, the perinatal mortality decreased to 3.4/1000 in 2009, and the low birth-weight rate and cesarean section rate increased according to the alternative b). Increase of centralization of preterm newborns under 1500 grams and improvement of their birth-weight specific early neonatal mortality (the factors which played the main role in decrease of perinatal mortality before) have already stopped. In the situation of further increase of low birth-weight rate and further deterioration of other negative factors we could expect increase of perinatal mortality above 4/1000. CONCLUSION: According to the two previous prognoses we observed improvements of perinatal care. While the reserves for the continuing improvement (medical and organizational) are already exhausted and while the conditions for provision of care are worsening, we could expect worse perinatal results in terms of further increase of low birth-weight rate, increase of cesarean section rate, and elevation of perinatal mortality above 4/1000.
Keywords: Czech Republic; Perinatal Care; Pregnancy; mezinárodní srovnání; lidé; ženské pohlaví; císařský řez; Cesarean Section; novorozenec s nízkou porodní hmotností; Female; Young Adult; Adult; novorozenec; Infant, Low Birth Weight; zajištění kvality zdravotní péče; Humans; Perinatal Mortality; dospělí; perinatální péče; Quality Assurance, Health Care; perinatální mortalita; mladý dospělý; těhotenství; Česká republika; Infant, Newborn